Central bank modernisation - Courtis, Neil.; Nicholl, P. W. E. (Peter W. E.) (London : Central Banking, 2005)
Provides information and ideas to help central banks focus on change management, not only as defined by the traditional disciplines or functions of central banking - monetary policy, payment systems, financial supervision, currency management - but also as broader, cross-cutting, central bank "management issues" - efficiency, governance, information technology and transparency.
Includes bibliographical references.
oif 30/01/15
Loan
Keywords: Banks and banking, Central